Factors associated with the performance of a blood-based interferon-γ release assay in diagnosing tuberculosis. - Sally Banfield (Public Library of Science (PLoS), 2012)
Background Indeterminate results are a recognised limitation of interferon-γ release assays (IGRA) in the diagnosis of latent tuberculosis (TB) infection (LTBI) and TB disease, especially in children. We investigated whether age and common co-morbidities were associated with IGRA performance in an unselected cohort of resettled refugees. Methods A retrospective cross-sectional study of refugees presenting for their post-resettlement health assessment during 2006 and 2007. Refugees were investigated for prevalent infectious diseases, including TB, and for common nutritional deficiencies and haematological abnormalities as part of standard clinical screening protocols. Tuberculosis screening was performed by IGRA; QuantiFERON-TB Gold in 2006 and QuantiFERON-TBGold In-Tube in 2007. Results Complete data were available on 1130 refugees, of whom 573 (51%) were children less than 17 years and 1041 (92%) were from sub-Saharan Africa. All individuals were HIV negative. A definitive IGRA result was obtained in 1004 (89%) refugees, 264 (26%) of which were positive; 256 (97%) had LTBI and 8 (3%) had TB disease. An indeterminate IGRA result was obtained in 126 (11%) refugees (all failed positive mitogen control). In multivariate analysis, younger age (linear OR= 0.93 [95% CI 0.91-0.95], P<0.001), iron deficiency anaemia (2.69 [1.51-4.80], P = 0.001), malaria infection (3.04 [1.51-6.09], P = 0.002), and helminth infection (2.26 [1.48-3.46], P<0.001), but not vitamin D deficiency or insufficiency, were associated with an indeterminate IGRA result. Conclusions Younger age and a number of common co-morbidities are significantly and independently associated with indeterminate IGRA results in resettled predominantly African refugees.